Effects of temperature on the intensive culture performance of larval and juvenile North American burbot (Lota lota maculosa) - Barron, JM; Jensen, NR; Anders, PJ; Egan, JP; Ireland, SC; Cain, KD (2012)
The objective of this study was to determine the effect of temperature on growth and survival of larval and juvenile burbot, Lota lota maculosa . Burbot aquaculture is developing primarily in response to declining wild stocks and a need to restore such populations. Beyond conservation efforts, there is also potential to culture this species commercially. However, many important aspects of burbot culture remain unaddressed. In this study larval and juvenile burbot were reared at three constant water temperatures (10, 15, and 20 °C) in an intensive culture setting. Two 30 day trials were conducted during the larval life stage and one 60 day trial during the juvenile life stage. In Trial 1, larval burbot (mean total length±SD, 6.9±1.0 mm, approximately 65 days post hatch) reared at 20 °C grew the fastest, while growth was lowest in the 10 °C treatment. Survival was inversely related to temperature, with the lowest average of 6.6% observed in larvae reared at 20 °C. The percentage cannibalized was quantified and found to be positively correlated with water temperature, and reached 58.0% in larvae reared at 20 °C. In Trial 2, as larvae approached metamorphosis (12.9±1.9 mm, approximately 100 days post hatch), growth was also highest in fish at 20 °C and lowest in those at 10 °C. At this stage survival was higher in fish at lower temperatures, but the percentage cannibalized appeared independent of temperature, averaging over 50% in fish at all temperatures. In Trial 3, growth of juveniles (59.9±12.4 mm, approximately 205 days post hatch) reared at 15 and 20 °C was not significantly different, yet both displayed significantly increased growth relative to juveniles reared at 10 °C. Juveniles were fully transitioned to a dry diet, and survival averaged >93% in all culture temperatures. The percentage cannibalized during this life stage averaged b5%, and was not affected by temperature. This study demonstrated the importance of water temperature, as it clearly affects culture performance of larval and juvenile burbot. ...